Return to play recommendations after COVID-19 diagnosis in high school athletes - Calpino, K.; Morrissette, J. (Journal of Athletic Training, 2021)
COVID-19 has drastically changed everyday life across the world and has dramatically impacted how athletics operate. Since the return of high school sports, high school athletic trainers are now responsible for ensuring the safe return of athletes previously diagnosed with COVID-19 to sports. Due to the relatively recent identification of this novel virus, very little is understood about the long-term effects of COVID-19 infection on the cardiac and respiratory systems. Due to the rapid return of athletics, there is unfortunately limited research available regarding how athletes respond to COVID-19 and how it may affect their ability to return to play. Therefore, it is recommended that high school athletes previously diagnosed with COVID-19 undergo a comprehensive medical evaluation with their physician and complete a graduated medically supervised return to play protocol.